Novel framework of integrated security and safety system using hybrid network technology - Saputra, Edi; Abu Bakar, Kamarulnizam; Herman, H.; Hassan, Suhaidi (IEEE Computer Society, 2009)
Advancement in Micro-Electro Mechanical System (MEMS) that integrate mechanical system, sensor, actuator, and electronics has contributed to significant improvement of automation system including security and safety system. This paper will propose a framework of integrated security and safety system that combines Micro Embedded System and Computer Based System. The framework is designed and developed based on conceptual model of security and safety system for enclosed area such as campus, industrial complex, airport, and oil/gas platform. As infrastructure for connecting the security and safety devices, control panels, and Network Operating Center (NOC), the framework will use Hybrid Networking Technology. Such technology interconnects IP-based and non IP network in form of wired and wireless data communication.